PENGARUH PEMBERIAN PELAYANAN INFORMASI OBAT DAN KONSELING TERHADAP TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS DENGAN HIPERTENSI DI RUMAH SAKIT DAERAH IDAMAN BANJARBARU - Satrio Wibowo Rahmatullah; Ika Maulida Nurrahma; Adnan Syahrizal (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Compliance to achieve treatment success can be improved by providing drug information services (PIO) and counseling to improve understanding of treatment instructions. The general objective of this study was to determine the effect of drug information service and counseling on the level of medication adherence in patients with diabetes mellitus (DM) with hypertension in the Banjarbaru Regional Hospital. This study uses a quasi experimental method with a cross sectional approach and takes patient data prospectively. The results of this study indicate that the group given PIO and counseling showed a high level of adherence as many as 20 respondents (100%). Whereas in the group that was not given PIO and the counseling level of adherence was low, there were 4 respondents (20%). Based on the mann-whitney analysis p-value = 0,000 (<Î± = 0.05) so that there are differences in the group with PIO and counseling with groups without PIO and counseling, while the chi square analysis p-value = 0.004 (<Î± = 0 , 05) so that PIO and counseling have a significant effect on the level of adherence to taking medication in patients with DM with hypertension at the Banjarbaru Regional Hospital.